Curriculum Management Based on Deep Learning to Improve Graduate Quality - Zainal Abidin; Ahmad Qusairi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study examines how immersive learning-based curriculum management contributes to improving graduate quality in an Islamic high school context. Using a qualitative case study approach at MA Riyadul Ulum Pasuruan, data were collected through in-depth interviews, classroom observations, and document analysis involving school leaders, teachers, staff, and students. Findings indicate that integrating immersive learning principles into curriculum planning, teaching practices, and assessment systems improves students' conceptual understanding, critical thinking, and active learning engagement. The most significant results indicate that the effectiveness of immersive learning is strongly influenced by institutional curriculum management, specifically teacher professional development, consistent policy alignment, and process-oriented assessment. The uniqueness of this study lies in positioning immersive learning not merely as a pedagogical strategy but as an integrated curriculum management framework within the madrasah system, aligning academic competencies and Islamic character education. This study contributes theoretically by expanding the discourse on Islamic education management beyond a normative perspective, and practically by offering a contextual model for developing a madrasah curriculum oriented toward sustainable graduate quality.